Therapists' attitudes to offering eCBT in an inner-city IAPT service: a survey study. (28th August 2018) - Meisel, Susanne F.; Drury, Helena; Perera-Delcourt, Ramesh P.
Abstract: Despite an emerging evidence base for the efficacy of supported computerized cognitive behavioural therapy (eCBT), uptake in services has been slow. Therapists' beliefs about eCBT may constitute a barrier to offering eCBT to clients, but little research has investigated this topic. The aim of this study was to investigate therapist attitudes towards eCBT in one inner-city Improving Access to Psychological Therapies (IAPT) service using a survey design. Data were analysed using descriptive statistics. Thirty-three therapists took part in the study. Although 97% of participants reported that they knew 'what eCBT involves', and 62% reported that they were 'confident to offer eCBT to clients', only 10% endorsed that 'there is a strong evidence-base to support the use of eCBT'. Two-thirds of the sample believed that eCBT 'could be effective for mild and moderate mental health difficulties', but most participants believed that eCBT would perform 'worse' or 'much worse' than face-to-face interventions for a range of disorders. Barriers to offering eCBT related predominantly to assumptions about client expectations of therapy, and perceived lack of a therapeutic relationship. Participants identified the provision of training on eCBT for those recommending treatment options to clients as a potential solution. Results from this study highlight therapists' attitudes to eCBT that might contribute to low uptake rates of eCBT. Particularly, misperceptions about the evidence base for eCBT may be prevalent. Appropriate training and ongoing supervision for therapists are considered as interventions that may increase acceptance of eCBT as a valid treatment option.